PERFORMANCE STUDY: THE EFFECT OF TRAINING AND MOTIVATION OF MEDICAL SUPPORT FUNCTIONAL STAFF - Harin, Sri; Ch, Irwan; Kartini, Tini; Yulianingsih; Suryadi, M. Asep (International Journal of Psychosocial Rehabilitation, 2020)
Medical support functional staff have an important role in hospital services and performance. This study aims to determine the effect of job training and work motivation on the performance of functional medical support staff in hospitals. The questionnaire was distributed to 62 respondents. The results of validity and reliability tests show that all questions are declared valid and reliable. The results of multiple correlation analyzes states that there is a strong relationship between job training and work motivation on employee performance, the results of the coefficient of determination can be explained as 63% of employee performance is influenced by job training and work motivation while 37% is influenced by other variables not examined in this study, such as employee ability. There is a positive and significant effect between job training and work motivation on functional medical support staff performance in the hospital, simultaneously and partially.